Public and private benefits in urban development agreements. - Oppio, Alessandra; Torrieri, Francesca (Springer, 2018)
The paper is aimed at exploring the advantages of public authorities within the context of negotiating Public Private Partnership (PPP). During recent years, many European cities have developed complex urban interventions through innovative forms of cooperation between the public and private sector. Given the limited public funds to cover investments and the need to increase the quality and efficiency of public services, this kind of PPP enables public and private sectors to define agreements with respect to future urban development interventions. Starting from an analysis of the urban developments under PPP carried out in Lombardy region over the last 15 years, the paper provides an overview of surplus values that result from land-use changes and development with the aim of pointing out the allocation between public and private parties. Despite the difficulty of performing an ex-post evaluation of surplus values, meaning the difference between the asset values before and after transformation, mainly for the limited and incomplete economic data recorded by the agreement, some preliminary insights are drawn, and a first operational framework is suggested to evaluate the sustainability of the urban development interventions from a public perspective.
Keywords: Stadtplanung; Stadtentwicklungsplanung; Infrastrukturpolitik; Wirtschaftsförderung; Öffentliche Hand; Investition; ÖPP